2021
DOI: 10.1155/2021/3656831
|View full text |Cite|
|
Sign up to set email alerts
|

Development of Refractive Parameters in 3- to 6-Year-Old Children and Its Application in Myopia Prediction and Intervention Guidance

Abstract: Objective. To investigate refractive development and prevalence of myopia in children aged 3-6 years in Hebei Province, China, and to explore the developmental law of refraction, so as to clinically guide the prediction and intervention of myopia. Methods. In May 2019, a total of 6120 people were inspected in 68 kindergartens in 11 cities in Hebei Province. Child refractive refraction was checked under noncycloplegia using a handheld binocular vision screener (SW-800, SUOER, Tianjin, China). Axial length (AL) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
4
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
3
4
1
Order By: Relevance
“…In the present study, male sex was associated with myopic SE, longer AL, and higher AL/CR ratio among children aged 4–6 years, consistent with previous studies ( 24 , 33 ). The AL and AL/CR ratio of boys were 0.43 mm and 0.03 higher than that of girls, respectively.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, male sex was associated with myopic SE, longer AL, and higher AL/CR ratio among children aged 4–6 years, consistent with previous studies ( 24 , 33 ). The AL and AL/CR ratio of boys were 0.43 mm and 0.03 higher than that of girls, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…In comparison of prevalence rates among different studies, the differences in definition of refractive error and urbanity of the area and refractive error measurement techniques should be noted. Zhang et.al reported that the prevalence of myopia (SE ≤ −0.75D) with non-cycloplegic autorefraction was 3.5% in 3–6-year -old children in Hebei Province, China ( 24 ). Meanwhile, Li et al reported that the prevalence of myopia (SE ≤ −1.00 D) with non-cycloplegic autorefraction was 5.9% in 4–6-year-old children in Shanghai ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…The mean value of AL/CR was 2.75 ± 0.13, which is similar to the findings of the recent study on the morbidity of hyperopia in 13513 children aged 6-72 months, with a mean AL of 21.53 ± 0.7mm, a mean CR of 7.71 ± 0.27mm and a mean AL/CR ratio of 2.79 ± 0.07 [2]. The mean SER value of 4.40 ± 2.48D in this study was significantly higher than the mean SER values of 0.67 ± 1.05D and 0.28 ± 0.82D for preschool children completing refractive screening without ciliary muscle paralysis in Henan [21] and Chengdu [22], further confirming that preschool children have a wide fluctuating range of latent hyperopia, which is highly concealed and easily missed by ordinary computerized optometry. We found that the SER values of children aged 3-6 decreased gradually.…”
Section: Discussioncontrasting
confidence: 63%
“…Zhang et al 10 In our study, between 4-7 years of age, average AL increase was 0.24 mm/year in males and 0.18 mm/year in females, and between 7-9 years of age, average AL increase was 0.36 mm/year in males and 0.51 mm/year in females. The increase in ALs in subjects aged 7-9 years was greater than that in subjects aged 5-7 years for both sexes.…”
Section: Discussionsupporting
confidence: 60%